Effect of single and combined median nerve stimulation and repetitive transcranial magnetic stimulation in patients with prolonged disorders of consciousness: a prospective, randomized, single-blinded, controlled trial - Xiong, Qi; Le, Kai; Tang, Yunliang; Ye, Wen; Wang, Yan; Zhong, Yuan; Zhou, Yao; Feng, Zhen (Frontiers in Aging Neuroscience, 2023)
Objective To investigate the efficacy of median nerve stimulation (MNS) combined with repetitive transcranial magnetic stimulation (rTMS), MNS alone, and rTMS alone in elevating the level of consciousness in patients with prolonged disorders of consciousness (pDOC). Participants and methods We enrolled 75 eligible inpatients suffering from pDOC as a result of traumatic or non-traumatic brain injury. Participants were randomly assigned to one of the following three treatment groups: (1) rTMS+sham-MNS; (2) MNS + sham-rTMS; or (3) MNS + rTMS. The rTMS protocol involved stimulation above the left dorsolateral prefrontal cortex at a 10 Hz frequency and 90% resting motor threshold. The MNS protocol involved the delivery of a 15–20 mA current at the median nerve point 2 cm from the wrist crease of the right distal forearm. The primary outcome was the change from baseline of the Coma Recovery Scale-Revised (CRS-R) score after treatment. Secondary outcomes included post-treatment changes from baseline of the Glasgow Coma Scale (GCS) score, awaken ratio, electroencephalography (EEG) scores, and the latency and amplitude of N20 on somatosensory evoked potentials. Results Before the intervention, there were no significant differences between groups in the CRS-R, GCS scores, age, duration of pDOC, clinical diagnosis, EEG scores, latency and amplitude of N20, sex, job, marital status, education level, or disease etiology. Within the three groups, the total CRS-R, GCS scores and amplitude of N20 on both side significantly increased and latency of N20 on poor side significantly decreased post-intervention. Significantly greater improvement in CRS-R, GCS total scores, amplitude of N20 on both side and latency of N20 on the poor side were observed in the MNS + TMS group compared to those of the groups receiving rTMS alone or MNS alone. The patients receiving TMS and MNS intervention showed a greater EEG activity improvement, and the EEG activity improved ratio significantly differ between groups, while there were no significant differences in the awakening ratios between the three groups. Conclusion The combination of MNS + rTMS was more efficacious in improving the level of consciousness than MNS alone or rTMS alone in patients with pDOC.